Detection of suspected carcinogen azo dyes in textiles using thermogravimetric analysis. Issue 8 (3rd July 2021) - Nguyen, Thao L.; Aparicio, Mario; Saleh, Mahmoud A.
Abstract: Textiles that are in direct contact with human skin are problematic due to the possibility of transferring the dyes or their aromatic amine metabolites through direct contact. 18 samples of women underwear panties of different colors and fabrics materials were examined for their content of azo dyes using thermogravimetric-gas chromatography-mass spectrometry (TGA-GCMS) technique. The nature of fabrics (cotton, nylon, and polyesters) was identified based on their unique thermogravimetric analyses (TGA) pattern. Aromatic amines produced from thermal degradation of the samples were identified using NIST mass spectra data base. Aniline was found in all samples regardless of their color or fabric composition. Black cotton textiles were characterized by the presence of diaminobenzene, red cotton sample showed the presence of 4-amino-3-nitrobenzene-1-sulfonic acid, blue cotton sample showed the presence of chlorobenzenediamine and chloroaniline, and purple cotton textiles showed the presence of 4-nitroaniline. All four purple nylon samples contained nitroaniline and biphenylamine, the three red nylon samples contained nitroaniline and methyldihydro-thiadiazole, the two pink samples showed the presence of chloro-2-(trifluoromethyl) anilinechloro- benzenediamine, the purple polyethylene sample show the presence of diphenyldiazene, and the brown polyester sample showed the presence of 2-amino-1, 4-phenylene) dimethanol.